Application Value of Gastroenterography Combined With CT in the Evaluation of Short-Term Efficacy and Prognosis in Patients With Esophageal Cancer Radiotherapy - Xue, Liangliang; E, Linning; Wu, Zhifeng; Guo, Dongqiang (Frontiers in Surgery, 2022)
Purpose To observe the application value of gastroenterography combined with CT in the evaluation of short-term efficacy and prognosis in patients with esophageal cancer radiotherapy. Methods From January 2013 to December 2020, the clinical data of 207 patients with esophageal cancer treated by radiotherapy in our hospital were collected retrospectively. All patients received gastroenterography and CT examination before and after radiotherapy, and the patients were followed-up for 1 year, and the evaluation value of their short-term efficacy and prognosis was observed. Results After radiotherapy, the length diameter, short diameter, and volume of the lymph node were lower than those before radiotherapy (p < 0.05), but the maximum tube wall thickness had no significant difference (p > 0.05). The length diameter, short diameter, and volume of the lymph node, and the maximum tube wall thickness in the good efficacy group and the good prognosis group were lower, and the objective response rate in the good prognosis group was higher (p < 0.05). The area under the curve (AUC) of the length diameter, short diameter, and volume of the lymph node to evaluate the short-term efficacy of patients with esophageal cancer was 0.738, 0.705, and 0.748, respectively, and the AUC to evaluate the prognosis of patients with esophageal cancer was 0.751, 0.776, and 0.791, respectively. Conclusion Gastroenterography combined with CT has a good application value in the evaluation of short-term efficacy and prognosis in patients with esophageal cancer radiotherapy.